The problematics of the Sitz im Leben of Qoheleth - Anderson, William H. U. (Old Testament essays, 1999)
Qobeleth is generally dated to the Ptolemaic period on the basis of linguistic analysis. However, in 1988 Fredericks challenged the status quo linguistic analysis of Qobeleth and argued that the book should be dated to the eighth or seventh century BCE. This paper provides a complementary perspective to Fredericks' challenge from a form-critical point of view. It discusses the problematics of the Sitz im Leben of Qobeleth and demonstrates the implausibility of the Ptolemaic or post-exilic setting for the book on the basis of its elitist and esoteric characteristics, historical problems relative to the internal content of the book, and faulty philosophical and intertestamental comparisons. It thus argues for an unspecified pre-exilic date for Qobeleth in the light of the problematics of a Ptolemaic or post-exilic setting for the book.